First Report of a Methicillin-Resistant, High-Level Mupirocin-Resistant Staphylococcus argenteus - Shittu, Adebayo Osagie; Layer-Nicolaou, Franziska; Strommenger, Birgit; Nguyen, Minh-Thu; Bletz, Stefan; Mellmann, Alexander; Schaumburg, Frieder (Frontiers in Cellular and Infection Microbiology, 2022)
We describe the identification of a methicillin-resistant, high-level mupirocin-resistant Staphylococcus argenteus. The isolate (1801221) was characterized as t6675-ST2250-SCCmecIVc, and whole-genome sequencing revealed that the isolate possessed two plasmids. One plasmid (34,870 bp), designated p1_1801221 with rep23, harboured the mupirocin resistance (mupA) gene. The second plasmid (20,644 bp), assigned as p2_1801221 with rep5a and rep16, carried the resistance determinants for penicillin (blaZ) and cadmium (cadD). Phylogenetic analysis revealed that the isolate clustered with the European ST2250 lineage. The overall high similarity of both plasmids in S. argenteus with published DNA sequences of Staphylococcus aureus plasmids strongly suggests an interspecies transfer. The acquisition of the mupA gene by S. argenteus highlights its clinical significance and the need for its correct identification.